Lviv during the Russian occupation of 1914–1915 in the light of the minutes of the magistrate presidium meetings and the journals of Zygmunt Russocki - Ślusarek, Krzysztof (City and War, 2021)
The article discusses some aspects of the functioning of the city authorities and the life of the inhabitants during the occupation of Lviv by the Russian army, in the period from September 3, 1914 to June 22, 1915. The basis for considerations is minutes from the magistrate presidium meetings and the journals of Zygmunt Russocki. The presidium of the city council of Lviv consisted of pre-war vice-presidents: Tadeusz Rutowski (as chairman), Leonard Stahl, and Filip Schleicher. The preserved minutes of the meetings of this committee show that in the last months of 1914 the most important task was to obtain loans for the current activities of the municipality. At the beginning of 1915, the presidium dealt with, inter alia, granting allowances for widows of city officials and establishing charity institutions that help the poorest inhabitants. In the diary of Zygmunt Russocki, the most important thing is the description of the situation in Lviv when the Russian troops entered the city. The author writes, among others about the concerns of the inhabitants, the behavior of Russian soldiers and officers, and the difficulties in providing food. He also mentions the war devastation of inland estates in the vicinity of Lviv and the impact of war propaganda on the attitudes of the inhabitants. Both documents used to supplement the existing knowledge about the Russian occupation of Lviv. At the same time, they indicate new areas of research, such as the care of municipal authorities over the families of former employees.